Addis Amba Mädhané Aläm: the Uncommon Troglodytic Heritage of Ethiopia - Tsegaye Ebabey DEMISSIE (Warszawskie Studia Teologiczne)
Ethiopia is one of the few African countries that have preserved the antiquities of early and medieval Christianity. The cave church of Addis Amba Mädhané Aläm (the church of Saviour of the World), is one of the little known troglodytic heritages found in Mäqét, North Wällo. This study aims to uncover the historical, architectural and artistic values of the cave church that has unique cultural testimonies. Data for the study were collected through fieldwork, interviews, and archival consultations. The cave is believed to have been excavated by Musé, the second bishop of Ethiopia. The church has six different caves cut into a rock face. Five of them are chapels, treasuries and gusting rooms. This paper discusses the cave which is the church of Mädhané Aläm. It has a complex layout compartmented into chanting room, holy and sanctuary. The holy and sanctuary form the nave which is rock-hewn monolithic feature detached from the main rock except on its roof and base. This planning is uncommon in the rock cave church tradition of Ethiopia because the nave is monolithically carved within a cave that should not be confused with churches built under a natural cave. The old enough canopy, a large artistic processional umbrella permanently projected over the chanting place also distinguishes this cave church. This is an indigenous piece of handcraft crafted locally from the bark of a tree. It is painted with different symbols and saint icons. The cave is also home to archaic mural paintings.